Determination of Optimal Route for Distribution of Rice Food Assistance in City X using the Cuckoo Search Algorithm - Eri Wirdianto; Muhamad Gustaffo Bintang; Farhan Azhari (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2026)
As distribution requirements become more complex, various VRP variants have been developed to address specific challenges. Among them, the Vehicle Routing Problem with Time Windows (VRPTW) adds the constraint that each customer must be served within a predefined time frame, making the routing process considerably more difficult. In this study, we propose a new approach that uses the Cuckoo Search (CS), a metaheuristic algorithm based on Lévy flights. This combination of Lévy flights and CS is designed to maximize exploration of optimal solutions while allowing dynamic route variations. This study aims to evaluate the effectiveness of this approach in optimizing rice food assistance distribution routes in City X. The exact method yielded a global optimum solution consisting of four routes with a minimum total distance of 222 km, requiring 2 hours 36 minutes 27 seconds of computation. In comparison, the cuckoo search algorithm also produced four routes, with a slightly longer total distance of 244 km but a significantly shorter computation time of 1 minute 39 seconds. This represents a difference of about 22 km (9.91%) from the exact solution, demonstrating that for VRPTW, the cuckoo search algorithm can generate near-optimal results with minimal deviation and substantially reduced computational effort.